The names of racism in Mexico: a lexical overview - Colín, Marisela (2023)
The purpose of the study is to analyse the names with which racism is designated in Mexico; as well as the relationship of its lexicon with phenomena such as ethnicism, discrimination and classism. The theoretical framework is built from research on current racism (Castellano, 2000; Gall, 2014, 2004), lexicological (Atunes, 2012; Lara, 2006) and discursive studies (Hall, 1992). To achieve the objective, we work with a corpus of opinion texts composed of 109 comments written anonymously in response to four trigger texts asking whether or not racism exists in Mexico and a mediating text that promoted the participation of readers of a Mexican Online newspaper. The data are studied in two phases: first, through a content analysis (Bardin, 2002) we work on the lexical level of the texts by identifying the topics and organizing them by semantic categories; second, they are analysed quantitatively using the AntConc.exe application (Anthony, 2022). The results show the denominations regarding racism, their most frequent semantic associations and the intersectionality that can be observed in everyday life.